Early increase in circulating carbonic anhydrase IX: A potential new predictive biomarker of preeclampsia - Galbiati, Silvia; Gabellini, Daniela; Ambrosi, Alessandro; Soriani, Nadia; Pasi, Federica; Locatelli, Massimo; Lucianò, Roberta; Candiani, Massimo; Valsecchi, Luca; Zerbini, Gianpaolo; Smid, Maddalena (Frontiers in Molecular Biosciences, 2023)
Preeclampsia (PE) is a severe complication of pregnancy. The identification of a reliable predictive biomarker could help in setting up a specific preventive strategy. To this aim, we studied carbonic anhydrase IX (CAIX) as a marker of hypoxia (a pathway involved in PE pathogenesis) and compared the diagnostic accuracy of CAIX to that of the validated biomarker sFlt1/PlGF ratio. Fifteen women with overt PE and 38 women at a risk of developing PE, sampled at different time intervals during gestation (a total of 82 plasma samples collected), were enrolled and underwent the CAIX measurement. CAIX levels significantly increased (p < .001) before the onset of the disease in women (25% of the total number) who later on developed PE when compared to women who did not, starting from 28th gestational week. The best CAIX cut-off of 68.268 pg/mL yielded a sensitivity of 100%, a specificity of 81.82%, and an AUC value of .9221. In our pilot study, when compared to the sFlt1/PlGF ratio, CAIX performed better in predicting PE before the clinical onset. Furthermore when implemented as CAIX/PlGF ratio, showed up to be comparable in the identification of women with overt early PE. In conclusion, CAIX could represent an effective predictive biomarker of PE, and larger studies are mandatory to validate this finding.